Pengaruh Physical Evidence Terhadap Kepuasan Pelanggan Pada Lapangan Pmc Futsal International In Court Tanjung Kabupaten Tabalong - Sulistiyono, Fulqi (Jurnal PubBis, 2026)
The development of the futsal sports service industry in Tabalong Regency shows an increasingly high level of competition, requiring facility managers to be able to provide optimal service quality. In intangible services, customers tend to use physical evidence as the main basis for assessing the quality of services received. Poorly maintained physical facilities, such as cleanliness, comfort, and the completeness of supporting facilities, have the potential to reduce customer satisfaction and affect the sustainability of sports services businesses. Based on these conditions, this study aims to analyze the effect of physical evidence on customer satisfaction at the PMC Futsal International In Court Tanjung in Tabalong Regency. This study uses a quantitative approach with a probability sampling method. The research population consisted of 156 customers registered as members, with a sample size of 62 respondents. Data collection was conducted through questionnaires and observation, then analyzed using simple linear regression. The results show that physical evidence has a positive and significant effect on customer satisfaction, with a coefficient of determination of 68.3%. These findings indicate that the cleanliness of facilities, the comfort of the environment, the completeness of supporting facilities, and the atmosphere of the service space play an important role in shaping customer perceptions and satisfaction thus, this study provides an overview that attention to the quality of physical evidence can help futsal field managers maintain customer satisfaction and sustainability